A Phase Ib Trial of Durvalumab in Combination with Trastuzumab in HER2‐Positive Metastatic Breast Cancer (CCTG IND.229). (16th August 2019) - Chia, Stephen; Bedard, Phillipe L.; Hilton, John; Amir, Eitan; Gelmon, Karen; Goodwin, Rachel; Villa, Diego; Cabanero, Michael; Tu, Dongsheng; Tsao, Ming; Seymour, Lesley
Abstract: Background: Immune checkpoint inhibitors are active in a broad range of cancers, including programmed death ligand 1 (PD‐L1)‐positive, triple‐negative, metastatic breast cancer (MBC). Antibody‐dependent cell‐mediated cytotoxicity is a mechanism of action of trastuzumab. We performed a phase Ib trial of durvalumab and trastuzumab in HER2‐positive MBC previously treated with chemotherapy and anti‐HER2 antibodies to assess safety, efficacy, and correlative endpoints. Patients and Methods: Patients with HER2‐positive MBC were enrolled on a standard 3 + 3 design. Dose level 1 was durvalumab (1, 125 mg intravenously day 1) and trastuzumab (8 mg/kg intravenously loading, then 6 mg/kg day 1) on a q3 weekly cycle. An expansion cohort at the recommended phase II dose (RP2D) performed tumor biopsies at baseline and after cycle 1. The primary endpoint was to establish the RP2D. Results: Fifteen patients were accrued from April to December 2016, of which 14 were evaluable for response. Median age was 54 years (range 40–86); the majority had visceral disease (87%) and at least three prior (adjuvant and/or metastatic) lines of chemotherapy (73%), including trastuzumab (93%), pertuzumab (60%), and trastuzumab‐emtansine (93%) for MBC. No dose‐limiting toxicities were observed at dose level 1 ( n = 6) or dose expansion ( n = 9) during cycle 1. One patient developed a grade ≥3 immune‐related adverse event (grade 4 diabetes mellitus). No responses by RECIST were seen, with 4 of 14 patients (29%) demonstrating stable disease as best response at week 6 (median duration, 2.7 months). All patients had <1% PD‐L1 expression on either archival tissue (7/15) or prestudy biopsy (8/15). In the dose expansion cohort, evaluable pretreatment and on‐treatment tumor biopsies ( n = 5) showed minimal CD8 cell infiltration. Conclusion: The RP2D of durvalumab and trastuzumab is standard full doses of both agents. No significant clinical activity was observed in patients with heavily pretreated HER2‐positive PD‐L1‐negative MBC. Implications for Practice: This phase Ib trial with associated correlative endpoints provides insights into the lack of activity of the combination of durvalumab and trastuzumab in heavily pretreated HER2‐positive metastatic breast cancer (MBC). No significant clinical activity was observed in patients with heavily pretreated HER2‐positive programmed death ligand 1 (PD‐L1)‐negative MBC with evidence of cytotoxic T‐cell exhaustion. Furthermore, all patients had no expression of PD‐L1 in the tumor cells. These data support the importance of PD‐L1 as an important selection biomarker and the need to assess the tumor microenvironment for immune regulatory cells. Further work is needed to understand how to activate the "cold" tumors to be able to combine current immune‐oncology agents. Abstract : HER2 directed therapies have improved prognosis for HER2‐positive breast cancer, although patients with advanced disease ultimately develop resistance. This article reports a phase Ib trial of durvalumab in combination with trastuzumab in resistant HER2‐positive advanced breast cancer.